Pengaruh Lingkungan Kerja, Konflik Kerja, Dan Budaya Organisasi Terhadap Kinerja Karyawan Pada Koperasi Simpan Pinjam Bangun Jaya Makmur Kantor Bogo - Alvionita Ayu Effendi, Nadia; Syahputra, Erwin; Sri Hardiningrum, Iing (Cahaya Ilmu Bangsa, 2025)
This research aims to determine the significance of the influence of the work environment, work conflict, and organisational culture on employee performance. This research was conducted at the Bangun Jaya Makmur Savings and Loan Cooperative, Bogo Office, Kediri Regency, East Java. The type of this research is quantitative research that includes a hypothesis as an initial assumption in the study. The sample size consisted of 30 respondents using the saturated sampling technique. The data analysis technique is multiple linear regression using SPSS version 25 software. The results of this study indicate that, partially, the work environment has a negative and significant impact on the performance of employees at the Bangun Jaya Makmur Savings and Loans Cooperative, Bogo Office, Kediri Regency. Work conflict has a negative and significant impact on the performance of employees at the Bangun Jaya Makmur Savings and Loans Cooperative, Bogo Office, Kediri Regency. Organisational culture partially has a negative and significant impact on the performance of employees at the Bangun Jaya Makmur Savings and Loans Cooperative, Bogo Office, Kediri Regency. Meanwhile, simultaneously, the work environment, work conflict, and organisational culture have a significant impact on the performance of employees at the Bangun Jaya Makmur Savings and Loans Cooperative, Bogo Office, Kediri Regency. Based on the research results, the coefficient of determination value in R Square is 0.722 or 72.2%, meaning that the work environment, work conflict, and organisational culture influence the performance variable of the savings and loan cooperative employees by 72.2%, and the remaining 27.8% of the performance variable of the savings and loan cooperative employees is influenced by other variables not examined by the researcher in this study, such as work motivation, work discipline, workload, and leadership support.